Effects of calcium-phosphate, laser and adhesive on dentin permeability and bond strength - Benitez Sellan, Pablo Lenin [UNESP]; Zanatta, Rayssa Ferreira; Gomes Torres, Carlos Rocha [UNESP]; Tian, Fu-cong; Bergeron, Brian E.; Niu, Li-na; Pucci, Cesar Rogério [UNESP] (Elsevier, 2020)
Objectives: The present study examined a technique for reducing dentin permeability through the application of a calcium phosphate (CaP)-based desensitiser with a laser-assisted process and evaluated adhesive-dentin bond strength. Methods: Thirty dentin discs were divided into two groups according to whether the selected desensitiser (TeethMate; Kuraray Noritake) was used prior to dentin bonding. Each group was subdivided into three subgroups (n = 5): A- Adhesive (Single Bond Universal, 3M ESPE), AL- Adhesive + Laser (Nd:YAG 60 mJ) and LAL- Laser + Adhesive + Laser. Dentin permeability values (%) were recorded before and after desensitiser application. Resin composites were placed over the bonded specimens; the latter were aged prior to microtensile bond strength evaluation. Gelatinolytic activity within the hybrid layers was examined with in-situ zymography using confocal laser scanning microscopy. Data were analysed with ANOVA and Tukey test (α = 0.05). Results: Significant differences in dentin permeability were identified for all groups (p = 0.00). Both laser treatment (p = 0.182) and desensitiser application (p = 0.687) did not significantly improve dentin bond strength. Ultrastructure of the resin-dentin interface identified presence of calcium phosphate within dentinal tubules. Laser treatment did not affect hybrid layer ultrastructure. Both treatment modalities (intratubular CaP occlusion and laser) had no influence on gelatinolytic activity within hybrid layers. Conclusion: Although intratubular CaP occlusion and laser treatment were effective in reducing dentin permeability, they did not affect bond strength, interfacial ultrastructure and gelatinolytic activity within hybrid layers. Clinical relevance: Treatment of etched dentin with Nd:YAG Laser at 60 mJ does not adversely affect collagen ultrastructure and gelatinolytic activity within the hybrid layer. The application of a calcium phosphate-based desensitiser to etch dentin does not affect dentin bond strength.

Materials science; Biomedical engineering; Bond strength; Calcium phosphate; Dentin permeability; Nd:YAG laser.
Keywords: Biomedical engineering; Bond strength; Calcium phosphate; Dentin permeability; Materials science; Nd:YAG laser